Driving customer appeal through the use of emotional branding - Garg, Ruchi, 1985-; Chhikara, Ritu; Panda, Tapan K.; Kataria, Aarti (IGI Global, Disseminator of Knowledge, 2018)
"This book explores how emotional branding is a unique branding strategy that touches consumer lives by influencing their thoughts and feelings to the extent that the brand gets positioned into the core of consumers' lives. It provides insights on how firms can benefit by adopting the same in the best manner applicable to their products and services"- Resumé vydavatel
Keywords: produktový management -- psychologické aspekty; řízení značky -- psychologické aspekty; spotřebitelské chování; product management -- psychological aspects; brand management -- psychological aspects; consumer behavior; elektronické knihy; sborníky; electronic books; papers of several authors